Longitudinal Characterization of Escherichia coli in Healthy Captive Non-Human Primates - Clayton, Jonathan B.; Danzeisen, Jessica L.; Trent, Ava M.; Murphy, Tami; Johnson, Timothy J. (Frontiers in Veterinary Science, 2014)
The gastrointestinal (GI) tracts of nonhuman primates are well known to harbor Escherichia coli, a known commensal of humans and animals. While E. coli is a normal inhabitant of the mammalian gut, it also exists in a number of pathogenic forms or pathotypes, including those with predisposition for the GI tract, as well the urogenital tract. Diarrhea in captive nonhuman primates (NHPs) has long been a problem in both zoo settings and research colonies, including the Como Zoo. It is an animal welfare concern, as well as a public health concern. E. coli has not been extensively studied in correlation with diarrhea in captive primates; therefore, a study was performed during the summer of 2009 in collaboration with a zoo in Saint Paul, MN, which was experiencing an increased incidence and severity of diarrhea among their NHP collection. Fresh fecal samples were collected weekly from each member of the primate collection, between June and August of 2009, and E. coli were isolated. A total of 33 individuals were included in the study, representing eight species. E. coli isolates were examined for their genetic relatedness, phylogenetic relationships, plasmid replicon types, virulence gene profiles, and antimicrobial susceptibility profiles. A number of isolates were identified containing virulence genes commonly found in several different E. coli pathotypes, and there was evidence of clonal transmission of isolates between animals and over time. Overall, the manifestation of chronic diarrhea in the Como Zoo primate collection is a complex problem whose solution will require regular screening for microbial agents and consideration of environmental causes. This study provides some insight towards the sharing of enteric bacteria between such animals.